2011
DOI: 10.1111/j.1442-9071.2011.02575.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous cavity haemorrhage post-vitrectomy for diabetic eye disease: the effect of perioperative anticoagulation and antiplatelet agents

Abstract: Perioperative continuation of anticoagulation or antiplatelet treatment appears to increase the risk of persistent postoperative vitreous cavity haemorrhage and the necessity for vitreous cavity washout in this diabetic cohort. Appropriate preoperative cessation of treatment appeared to reduce this risk; however, caution must be taken with regard to the systemic risk associated with cessation of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 26 publications
1
26
2
1
Order By: Relevance
“…In diabetic patients maintained on anticoagulant or antiplatelet therapy who had vitrectomy for vitreous haemorrhage, a postoperative dense VCH was found in 27.6% by Fabinyi et al . and in 11% by Brown and Mahmoud . Of the diabetic patients in our study who had vitrectomy for vitreous haemorrhage, we found a 10% (3/30) rate of postoperative dense VCH.…”
Section: Discussionmentioning
confidence: 43%
“…In diabetic patients maintained on anticoagulant or antiplatelet therapy who had vitrectomy for vitreous haemorrhage, a postoperative dense VCH was found in 27.6% by Fabinyi et al . and in 11% by Brown and Mahmoud . Of the diabetic patients in our study who had vitrectomy for vitreous haemorrhage, we found a 10% (3/30) rate of postoperative dense VCH.…”
Section: Discussionmentioning
confidence: 43%
“…Therefore, decision regarding maintenance or perioperative discontinuation of anticoagulation therapy should be made before vitrectomy by having appropriate consultations about patients’ systemic conditions. [351352353]…”
Section: Resultsmentioning
confidence: 99%
“…This applies to diabetic and non-diabetic patients undergoing vitrectomy 29 30. The risk of haemorrhage might be reduced with smaller incision procedures 31…”
Section: Discussionmentioning
confidence: 99%